Seafloor geomorphology of the northern Argentine continental slope at 40-41° S mapped from high-resolution bathymetry - Principi, Sebastián; Palma, Fermin Ignacio; Bran, Donaldo Mauricio; Bozzano, Graziella; Isola, José Ignacio; Ormazabal, Juan Pablo; Esteban, Federico Damián; Acosta, Luana Yazmin; Tassone, Alejandro Alberto (Journal of South American Earth Sciences)
The southern sector of the northern Argentine continental margin (NACM), extending from 40 to 41° S, corresponds to a previously unmapped area of the South Atlantic Ocean in term of high-resolution bathymetry. Newly acquired high resolution data in the slope sector of the NACM between 900 and 5000 m allowed us to carry out a geomorphological analysis by combining novel multibeam data with a very high-resolution 3D seismic-derived bathymetry. The resultant digital elevation model revealed the presence of a wide variety of seafloor features and allowed us to characterize them by a geomorphometric analysis. Along slope processes, produced by the interaction of contour currents with the seafloor, make up a large array of erosional and depositional elements on the slope, including a contourite terrace, scours, drift bodies and sediment waves, that as a whole form part of a Contourite Depositional System (CDS). Additionally, across slope processes are also present, and give origin to four deeply incised submarine canyons that intersect the CDS. Overall, this work reveals the geomorphological complexity of this sector of the NACM and serves as a reference point for further studies regarding the sedimentary processes and oceanographic dynamics acting in the continental slope. Fil: Principi, Sebastián. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina. YPF - Tecnología; Argentina Fil: Palma, Fermin Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y ...